ANALYSIS OF INCREASING WOMEN ENTREPRENEURSHIP’S - Kartika Dewi Permatasari; Ratna Suryani (STIE Pelita Nusantara Semarang, 2023)
Entrepreneurship is not only done by men but also by women. The role of women in business is also closely related to increasing creativity and innovation in problem-solving and efforts to seize opportunities that people face every day. Given the weak socio-economic situation and the difficulty of finding work, this situation increases opportunities for women to find and start private businesses with flexible capital based on their ideas and skills. This research was conducted in the District of Banjarnegara using a targeted sampling method and utilized the snowball sampling method for data collection, with a total of 50 respondents. The analytical method used in this study is descriptive statistics, classical assumption test, and regression test, but the hypothesis in this study is tested using the T-test and F-test. The results showed that capital, independence, emotional, understanding of accounting, and entrepreneurship education had a positive and significant effect on women in entrepreneurship, which means that these factors influenced women in entrepreneurship.